Comparative study on the seismic behaviour of assembled composite walls with vertical joint rigid connections and ductility connections. (May 2023) - Miao, Xinwei; Huang, Wei; Quan, Wenli; An, yongjiannan; Zhang, Jiarui
Abstract: To investigate the efficient dry connection type of fully assembled composite (FAC) walls, two novel vertical joint connection types, including rigid connections (box connections) and ductile connections (U-shaped plate connections), are proposed. In the experiment, three specimens were constructed and tested under in-plane reversed cyclic loading, including specimens with box connections (FAC-B) and U-shaped steel plate connections (FAC-U) and a specimen with a horizontal cast-in-place assembled composite (CAC) wall as the reference specimen. In the reversed cyclic loading test, the failure mode, hysteretic behaviour, bearing capacity, stiffness degradation and energy dissipation capacity were obtained. The test results indicated that the failure mode of all specimens was shear failure. In addition, a finite element model (FEM) of FAC-U is subsequently established and validated to further investigate the seismic performance of the plate thickness, concrete strength, compression ratio and block strength on the bearing capacity and ultimate displacement.